The effect of external environment on the process of decision-making associated with the closing of private industrial firms: The Iraqi experiment, (1976-1985) (Journal of the College of Education for Women, 2019)
Abstract The research hypothesizes is that the external Environmenthas the responsibility concerning decisions making and behavioralupon industrial firms. It is, Furthermore, an attempt to review theproblem of closures of private industrial firms in the country, duringthe period (1976-1985), i.e. prior to and during the Iraqian- Iranianwar. The behavioral approach of industrial geography has beenadopted as a theoretical background and the statistical test hasbeen practiced for the applied purposes. As result, the research comes out with suggestions,depending upon previous trials in the field of direction andformulation of the of the private industrial sector. The chief pointamong these suggestions is that the coordination of this sectorwith the currently changes in the world economy today is stronglyrequired.